Early substance consumption and problematic use of video games in adolescence - Coëffec, Adélaïde; Romo, Lucia; Cheze, Nathalie; Riazuelo, Hélène; Plantey, Sophie; Kotbagi, Gayatri; Kern, Laurence (Frontiers in Psychology, 2015)
Substance use as well as use of video games is frequent among young people. The purpose of this research was to study the links between the use of video games and the consumption of various substances such as alcohol, tobacco or cannabis at adolescence. In order to do so, 1423 students from middle and high schools filled an auto-questionnaire that included questions on age, gender, year of study, use of video games and consumptions of alcohol (AUDIT-C), tobacco (HSI) and cannabis (CAST). We found that 92.1% of teens use video games and 17.7% have a problematic use of video games (PUVG). Furthermore, results show that substance consumption seems frequent with 19.8% and 8.3% of participants having hazardous alcohol and cannabis consumptions respectively and 5.2% having a moderate to high tobacco dependence. Video gamers consumed significantly more alcohol and gamers with PUVG started their substance consumption (alcohol, tobacco and cannabis) earlier. PUVG was found to be negatively correlated to age at first substance consumption, but positively correlated to the time spent playing video games. However, it was not correlated to risks of substance dependence (scores of AUDIT-C, HSI and CAST). Finally, our results are consistent with the literature, in regard to frequency of substance use and use of video games in adolescence. These data will allow for a better consideration of prevention strategies and future care in this particular field.